Respuesta :

Answer:

The answer to your question is:

x 1 = -0.65

x2 = 7.65

Step-by-step explanation:

Equation              -x² + 7x + 5 = 0

a = -1

b = 7

c = 5

Quadratic formula     x = -b ±√(b² -4ac) / 2a

                                   x = - 7 ± √(7² -4(-1)(5) / 2(-1)

                                   x = -7 ± √(49 + 20) / -2

                                  x = -7 ± √69 / -2

                                   x = - 7 ± 8.3 / -2

               x1 = -7 + 8.3 / -2                         x2 = -7 -8.3 / -2

               x 1 = -0.65                                  x2 = 7.65